The strategic expression of the personal and general belief in a just world - Alves, H. (2014)
Previous research has shown that both the personal and the general belief in a just world (BJW) are judgment norms. This finding raises the possibility of a strategic component in the expression of the BJW. In the two studies reported in this article we investigated this possibility, specifically that the expression of BJW could be used to distinguish oneself from others and to convey specific images. In Study 1, we asked participants to fill in the personal and the general BJW scales on their behalf and according to the way they thought that their classmates would. The results showed that personal BJW was used as a device to distinguish the self from others. In Study 2 we asked the participants to fill in both BJW scales either according to their opinion or in order to convey a specific image: being likable, competent, successful, or pitiful. The results showed that personal BJW scores in the control condition and in all positive image conditions were higher than those in the "pitiful image'' condition. In the case of general BJW the same pattern only showed up when scores of personal BJW were not controlled for.